Interpretation of bone marrow aspiration in hematological disorder - S Pudasaini; KBR Prasad; SK Rauniyar; R Shrestha; K Gautam; R Pathak; S Koirala; U Manandhar; B Shrestha (Association of Clinical Pathologists of Nepal, 2012)
Background: Hematological disorders are quite frequent in all age group. Most of this hematological disorder first present as anemia. Bone Marrow Aspiration plays a major role in the diagnosis of its underlying cause. The aim of this study was to analyze the causes of hematological disorders, its spectrum and to interprete the bone marrow aspiration findings. Materials and Methods: This was a retrospective and prospective study carried out in the department of Pathology of Nepal Medical College in a period of two years. (July 2010 - June 2012). Bone marrow examination of 57 cases of suspected hematological disorders was carried out. All details of the patients were obtained from the record file in the department of pathology. Results: Out of 57 cases of bone marrow aspiration, erythroid hyperplasia was seen in 12 cases (21%). Megaloblastic anemia was seen in 7 cases (12.3%) and microcytic anemia was seen in 4 cases (7%). There were 6 cases (10.5%) of Idiopathic Thrombocypenic Purpura. Acute leukemia was diagnosed in 7 cases (12.3%) and among this acute myeloid leukemia (10.5%) was more common than acute lymphoid leukemia (1.8%). Myelodysplastic syndrome and multiple myeloma was seen in 3.5 % cases each. Aplastic anemia and kalaazar was seen in 5.3% and 1.8% cases respectively. Conclusion: Bone marrow examination is an important step to arrive at the confirmatory diagnosis of many hematological disorders. Journal of Pathology of Nepal (2012) Vol. 2, 309-312 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6885